Forward Lease Sukuk in Islamic Capital Markets Structure and Governing Rules - Lahsasna, Ahcene (Springer International Publishing, 2018)
This book focuses on forward lease sukuk, which is one of the most viable and dynamic Shari'ah-compliant instruments in the Islamic capital market. The idea of forward lease sukuk is to raise funds from non-existent assets whose subject matter does not exist at the time of the sukuk issuance. This book discusses the significant features of forward lease sukuk and demonstrates its vital contribution to project construction and manufacturing within the expanding field of Islamic finance.